Pertimbangan Putusan Hakim Perkara Harta Bersama di Pengadilan Agama Tembilahan - Azmil Fauzi Fariska (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2021)
This research was motivated by the decision of the Tembilahan Religious Court judges who decided the joint property case in which the judge decided the Plaintiff (husband) got 1/4 while the Defendant (wife) got 3/4 of the shared property. However, Article 97 in the Compilation of Islamic Law states that: "Widows or widowers are each entitled to half of the joint property as long as it is not stipulated otherwise in the marriage agreement." This research is in the form of library research using case No.0233/Pdt.G/2018/PA.Tbh, as the primary reference, while the secondary material in this paper consists of laws and regulations related to the object of the research decision No. 0233/Pdt.G/2018/PA.Tbh as well as books, journals, scientific works related to the object of research. The author's data collection technique uses interview techniques and study documents or library materials. The results of the verdict research are in accordance with the judge in deciding the case based on Legal Certainty (legal certainty) and Legal Justice (legal justice), legal certainty is what has been outlined by the laws and regulations, Compilation of Islamic Law, like this case according to legal certainty then the distribution it is the wife gets 1/2 and the husband also gets 1/2 then if only this which is applied rigidly in the case will reduce the values of justice itself, thus the judge in determining the joint property case uses Legal Justice.